2015
DOI: 10.1080/15374416.2015.1012720
|View full text |Cite
|
Sign up to set email alerts
|

Mediators and Treatment Factors in Intervention for Children Exposed to Interparental Violence

Abstract: Changes in children's emotion differentiation, coping skills, parenting stress, parental psychopathology, and parent-child interaction were explored as mediators of treatment factors in two selective preventive group interventions for children exposed to interparental violence (IPV) and their parents. One hundred thirty-four IPV-exposed children (ages 6-12 years, 52% boys) and their parents were randomized to an IPV-focused or common factors community-based group intervention and completed baseline, posttest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 53 publications
3
33
0
11
Order By: Relevance
“…Jouriles and colleagues (2009) found that changes in mothers’ inconsistent and harsh parenting partially accounted for Project Support’s effects on children’s conduct problems during treatment. In addition, consistent with the results of research on other interventions for children exposed to IPV (Graham-Bermann et al, 2007; Overbeek, De Schipper, Willemen, Lamers-Winkelman, & Schuengel, 2015), reductions in mothers’ trauma symptoms and psychological distress contributed to treatment effects. Yet, a sizable proportion (46.4%) of Project Support’s effects on children’s conduct problems cannot be attributed to changes in maternal parenting and maternal symptoms of trauma and distress, raising the question of what else might account for the improvements in child conduct problems.…”
Section: Interventions For Children Exposed To Ipv and How They Worksupporting
confidence: 73%
“…Jouriles and colleagues (2009) found that changes in mothers’ inconsistent and harsh parenting partially accounted for Project Support’s effects on children’s conduct problems during treatment. In addition, consistent with the results of research on other interventions for children exposed to IPV (Graham-Bermann et al, 2007; Overbeek, De Schipper, Willemen, Lamers-Winkelman, & Schuengel, 2015), reductions in mothers’ trauma symptoms and psychological distress contributed to treatment effects. Yet, a sizable proportion (46.4%) of Project Support’s effects on children’s conduct problems cannot be attributed to changes in maternal parenting and maternal symptoms of trauma and distress, raising the question of what else might account for the improvements in child conduct problems.…”
Section: Interventions For Children Exposed To Ipv and How They Worksupporting
confidence: 73%
“…However, this does not preclude the study of crucial change processes during therapy, which indeed is also on-going both in terms of examining insession client responses (e.g., de Kleine et al 2017;Sripada and Rauch 2015) and particular treatment components (e.g., Deblinger et al 2011;Sack et al 2016). Mechanisms of change and treatment elements can also be studied in tandem, as Overbeek et al (2017) did among children who had experienced interparental violence. Their approach of studying the effects of different degrees of exposure to specific and non-specific treatment elements as potentially mediated via different mechanisms can be recommended as highly informative about the relationships between therapy change processes and mechanisms of change beyond therapy.…”
Section: Mechanisms Of Change and Therapy Change Processesmentioning
confidence: 99%
“…all lead to reduction in symptoms. At the same time, isolating more treatment-specific mechanisms can boost our confidence in particular interventions, as we are able to ascertain that their effectiveness is indeed due to the mechanisms of change they specifically target (Kazdin 2007;Overbeek et al 2017). Such particular evidence may also help persuade clinicians to adopt empirically supported treatments (Tryon 2005).…”
mentioning
confidence: 94%
“…1 Hence, the divorce affects the compatibility of couples and their children in all aspects (psychological, physical, social and emotional) and decreases the performance and inefficiency of family members after divorce. 2 As one of the most stressful resources, divorce can disrupt the cognitive structures of individuals making them unable to use stress management methods. 3 This phenomenon has economic, social and, especially psychological harmful effects on women.…”
Section: Introductionmentioning
confidence: 99%